MODEL KONSEPTUAL KEPEMIMPINAN, GENDER, DAN DIVERSITAS - Poppy Nurmayanti; Evi Suryawati; Yohannes Firzal; Sinta Ramaiyanti; Yusni Maulida (Jurnal EL-RIYASAH, 2021)
This paper presents a conceptual model on leadership, gender, and diversity toward decision making with using role congruity theory. This paper also explore generally whether and why gender may matter for leadership and evaluate views on a feminine/masculine in effectiveness leadership. Recently, considerations of gender and diversity have predominantly focused on differences and similarities between female and male leaders that results from the difference between stereotypes and leadership stereotype. These difference exist worldwide and globalization of management brings to the need to examine this stereotype phenomenon in cross cultural area.